African scholarship and visa challenges for Nigerian academics (2013)
Twenty-first-century societies are driven by knowledge. But knowledge regimes in the world today are not balanced, which leads to dubious knowledge, poor recommendations, and vacuous conclusions in the areas of policy and practice. This is manifested in and closely related to the compromised academic mobility of African scholars, which has become topical and in need of attention across the global knowledge domains. African scholarship and scholars do not easily move across space and time to cross fertilize ideas and knowledge. African academic talents are thus at the margins of global scholarship and are poorly rated. Many find it difficult to participate in international academic activities due to difficulty in obtaining a visa to travel to the West, which is regarded as the locus of true knowledge production and dissemination. Unfortunately, primary research on dynamics, complexities, and contours of African academic mobility, particularly to the West, is scanty, fragmented, and largely anecdotal, which necessitates more robust and contemporary knowledge. This empirical article is set in Nigeria, Africa’s most populous country, and the country with the greatest number of universities on the continent. Primary data were collected through qualitative in-depth interviews (IDIs). Three prominent universities were selected for the study: University of Ibadan, Ahmadu Bello University, and Lagos State University. Sources of secondary data were unclassified official documents and scholarly publications.